2x+2−3x−3
2x−2+3x−3
2x−3−3x−2
5x−3−4x−2
Correct answer is B
5x−12(x−2)(x−3)=Ax−2+Bx−3
= A(x−3)+B(x−2)(x−2)(x−3)
⟹5x−12=Ax−3A+Bx−2B
A+B=5...(i)
−(3A+2B)=−12⟹3A+2B=12...(ii)
From (i), A=5−B
3(5−B)+2B=12
15−3B+2B=12⟹B=3
A+3=5⟹A=2
5x−12(x−2)(x−3)=2x−2+3x−3
The sine, cosine and tangent of 210o are respectively ...
A ship sails 6km from a port on a bearing 070° and then 8km on a bearing of 040°. Find the d...
Factorize m3 - 2m2 - m + 2 ...
Express (0.0439÷3.62) as a fraction....
Find the maximum value of y in the equation y = 1 - 2x - 3x2 ...
Divide the sum of 8, 6, 7, 2, 0, 4, 7, 2, 3, by their mean ...